Implementation of inventory policy in local government units - Modrzyński, Paweł; Voss, Grażyna (Scientific Papers of Silesian University of Technology. Organization and Management Series, 2023)
Purpose: The aim of this article is to present the determinants of a properly conducted inventory process in local governments and to demonstrate the role of local Government Shared Service Centers (SSCs) in improving the quality of the inventory process. Design/methodology/approach: The authors, based on a research tool - a case study, presented the results of inventory conducted in a rural municipality using a selected municipality in the Kuyavian-Pomeranian Voivodeship as an example. The inventory process was preceded by an analysis and development of appropriate internal documents, as well as employee training. After the inventory was completed, surveys were conducted among the employees involved in this process. The collected responses and the conducted literature studies, especially the analysis of post-control findings of national control organizations such as the Regional Audit Offices, allowed for drawing conclusions and achieving the set research goal. Research limitations/implications: The conducted studies on the literature related to the subject and the available post-control findings in the area of public finances of local government units allow for drawing conclusions regarding the complexity of the inventory process. Despite the legally and substantively well-defined process of conducting inventory in the Accounting Act, public entities, and particularly the local government units examined in this article, still make many mistakes in this process. The inventory process is especially crucial for the accurate preparation of financial statements for entities, including local government units. Originality/value: The research highlights the need to distinguish between the organizational and substantive aspects of the inventory process. While local government units can handle the substantive part (selecting proper methods and principles for individual assets), the organizational aspect poses challenges, especially in rural municipalities with complex structures and limited staff. The study reveals the close connection between the inventory process and internal documents like Municipal Office Regulations, employee records, and asset responsibilities. The findings identify problematic areas in the inventory process. The authors suggest that utilizing SSCs could enhance efficiency and security. Keywords: inventory, Local Government Shared Services Centers, public finance, public management. Category of the paper: research paper.